Motor vehicle crashes in pregnancy: Maternal and fetal outcomes. Issue 5 (26th May 2021) - Owattanapanich, Natthida; Lewis, Meghan R.; Benjamin, Elizabeth R.; Wong, Monica D.; Demetriades, Demetrios
Abstract : BACKGROUND: Motor vehicle crashes (MVCs) are a leading cause of death in pregnant women. Even after minor trauma, there is risk of fetal complications. The purpose of this study was to compare injuries and outcomes in pregnant with matched nonpregnant women after MVC and evaluate the incidence and type of pregnancy-related complications. METHODS: Retrospective study at a Level I trauma center included pregnant MVC patients, admitted 2009 to 2019. Pregnant patients were matched for age, seatbelt use, and airbag deployment with nonpregnant women (1:3). Gestation-related complications included uterine contractions, vaginal bleeding, emergency delivery, and fetal loss. RESULTS: During the study period, there were 6, 930 MVC female admissions. One hundred forty-five (2%) were pregnant, matched with 387 nonpregnant. The seat belt use (71% in nonpregnant vs. 73% in pregnant, p = 0.495) and airbag deployment (10% vs. 6%, p = 0.098) were similar in both groups. Nonpregnant women had higher Injury Severity Score (4 vs. 1, p < 0.0001) and abdominal Abbreviated Injury Scale (2 vs. 1, p < 0.001), but a smaller proportion sustained abdominal injury (18% vs. 53%, p < 0.0001). Mortality (1% vs. 0.7%, p = 0.722), need for emergency operation (6% vs. 3%, p = 0.295) or angiointervention (0.3% vs. 0%, p = 0.540), ventilator days (3 vs. 8, p = 0.907), and intensive care unit (4 vs. 4, p = 0.502) and hospital length of stay (2 vs. 2, p = 0.122) were all similar. Overall, 13 (11.1%) patients developed gestation-related complications, most commonly uterine contractions (6.3%), need for emergency delivery (3.5%), and vaginal bleeding (1.4%). CONCLUSION: Most pregnant patients hospitalized for MVC suffered minor injuries. Pregnant women had lower Injury Severity Score and abdominal Abbreviated Injury Scale than matched nonpregnant women. However, there was still a considerable incidence of gestation-related complications. It is imperative that pregnant patients be closely monitored even after minor trauma. LEVEL OF EVIDENCE: Prognostic and epidemiological, level III